Social factors in human actions - Hausner, Jerzy (Journal of Public Governance, 2014)
In the article the author poses the following questions: How do people actually act? What factors infl uence human action? How do people perceive their own action? To what extent does the way they perceive their own actions infl uence such actions? What would be the consequences of people acting exactly as they think they did?In order to address those issues, in the course of his argumentation the author comes to the following conclusion: in a social context, human actions do not need to be considered as belonging in the category of homeostasis or as leading to a balance. Th e actions result from tension and their aim may be its alleviation, but they always lead to a transition from one form of tension to another. Not only do they defuse energy, they also produce it.